Why Competitive Intelligence Fail: Interrogating the Correlates of CI Failure in the Nigerian Brewery Industry - Ngboawaji Daniel Nte; Kenneth Nduka Omede; Shad Ahmad Khan (Jurnal Ekonomi Akuntansi dan Manajemen, 2023)
Globally, as businesses grapple with uncertainties and challenges of growth and expansion, competitive intelligence failure has remained an obvious reality. This work therefore attempts to evaluate the intervening variables underlying the menace of competitive intelligence failure in the business world. Specifically, the study identifies the factors responsible for CI failures in the brewery industry in Nigeria. The identified factors include; lack of planning and management skills by managers and top company executives, faulty business decision making process and implementation by management and lack of coordinated organisational culture and political climate in the brewery industry in the country. In reaching these analytical premises, the study adopted a quantitative evaluation of some breweries in Nigeria to determine the pattern and trends of the competitive intelligence correlates and offered corresponding recommendations that will help to mitigate the menace of competitive failure in Nigeria. Key Words: Competitive Intelligence, Correlates, Failure, Nigeria, Brewery Industry